2017
DOI: 10.1242/dev.152413
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling transcriptome dynamics in human spermatogenesis

Abstract: Spermatogenesis is a dynamic developmental process that includes stem cell proliferation and differentiation, meiotic cell divisions and extreme chromatin condensation. Although studied in mice, the molecular control of human spermatogenesis is largely unknown. Here, we developed a protocol that enables next-generation sequencing of RNA obtained from pools of 500 individually laser-capture microdissected cells of specific germ cell subtypes from fixed human testis samples. Transcriptomic analyses of these succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
152
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(175 citation statements)
references
References 85 publications
14
152
0
5
Order By: Relevance
“…3B, ). We therefore looked more closely at the expression of genes that we previously found to be upregulated during the leptotene/zygotene to pachytene transition (Jan et al, 2017). This analysis first revealed that many genes from this gene set were not upregulated in type I or type II arrested spermatocytes but remained at leptotene/zygotene-like expression levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3B, ). We therefore looked more closely at the expression of genes that we previously found to be upregulated during the leptotene/zygotene to pachytene transition (Jan et al, 2017). This analysis first revealed that many genes from this gene set were not upregulated in type I or type II arrested spermatocytes but remained at leptotene/zygotene-like expression levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, we used the transcriptome of early pachytene spermatocytes, collected in a previous study describing gene expression throughout normal spermatogenesis (Jan et al, 2017), as controls. In this study, almost all genes characteristic for meiosis appeared to be already expressed in early spermatocytes, with early and late spermatocytes only displaying 24 DEGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Newly arisen male-biased genes are often X-linked, but over time the movement of these genes from the X to the autosomes has led to the de-enrichment of X-linked male meiotic genes [46]. Meiotic silencing may also select for X-linked genes that are critical in the later stages of meiosis to be highly expressed earlier in development (prior to meiosis or in early meiosis), so that transcripts persist through MSCI [48,49]. If true, then the constraints of MSCI may partially explain the enrichment for X-linked genes that are expressed earlier in spermatogenesis.…”
Section: Meiotic Phase: the Constraint Of Silenced Sex Chromosomesmentioning
confidence: 99%
“…DNA becomes highly condensed and the morphological features of the mature spermatozoa take shape through the process of spermiogenesis (Figure 1A). Spermiogenesis is a highly specialized developmental process and many genes expressed during this phase are specific to postmeiotic cells [48,49,71,72]. Similar to MSCI, sex-linked genes are also partially silenced during postmeiotic development through a process known as postmeiotic sex chromosome repression (PSCR) .…”
Section: Postmeiotic Phase: Conflict Between the X And Ymentioning
confidence: 99%